The Influence of Digital Service Quality and Customer Experience on User Satisfaction and Loyalty of Shopee in Indonesia Using SEM–PLS - Diva Dinar Fasya; Herdianto Herdianto; Syauqi Ahtisya; Jerry Heikal (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to analyze the influence of digital service quality and customer experience on user satisfaction and loyalty among Shopee users in Indonesia using the Structural Equation Modeling–Partial Least Squares (SEM–PLS) approach. Digital transformation has reshaped consumer behavior, positioning service quality and customer experience as key success factors in e-commerce. Data were collected through an online survey using a Likert scale from active Shopee users. The results indicate that customer experience has the most dominant influence on satisfaction, while digital service quality acts as a fundamental factor shaping users’ positive perceptions of the platform. Customer satisfaction is proven to be a significant mediating variable linking service quality and customer loyalty. Users who experience positive and consistent interactions tend to be more satisfied and demonstrate stronger long-term loyalty to Shopee. These findings highlight the importance of enhancing digital experiences that are both engaging and personalized to sustain customer loyalty in an increasingly competitive e-commerce environment.